Simulation of Regimes of Charge/Discharge in Batteries of Lead-Acid or of Lithium-Ion - Pereira, Nuno (2016)
The paper is about a dynamic simulation of charge and discharge on two battery technologies: the lead-acid battery model, and the lithium-ion battery model. The simulation aim is to evaluate the performance of the two battery technologies. Additionally, for both batteries, the hysteresis between the charge and discharge voltage is analysed. Simulations reveal that the lead-acid battery has a significant higher hysteresis than the lithium-ion battery.